Speech Acts Found in Inaugural Addresses of Barack Obama - Widya Oktarini (Universitas Muhammadiyah Jember, 2019)
This research analyzes the speech acts and language style found in inauguraladdressess of the presidents of The United States; Barack H. Obama. Thisresearch aims at describing kinds and functions of speech acts, the complianceand violation of cooperative principle. This research is descriptive qualitativeusing socio-pragmatics approach. In collecting the data, it uses simak methodand note-taking technique. In analyzing the data, it uses contextual methodby using socio-pragmatics theory. In presenting the results of the analysis, ituses informal method by verbal language. The results of the analysis showed:(a) there were six kinds of speech acts found in the inaugural addresses,specifically: assertive, directive, comissive, expressive, and declarative in whichdeclarative found in Obama’s second inaugural address with one data only (b)the functions of speech acts found are: (i) to give opinion, (ii) to inform, (iii)to give direction, (iv) to promise, (v) to express feelings (vi) to declare and to(vii) maintain relationship.